The Social Life of Jewish Music Records from 1948 Czechoslovakia by Hazzan Josef Weiss - Seidlová, Veronika (Lidé města, 2022)
This article traces transnational “life” trajectories of two rare Jewish religious music records from 1948 Communist Czechoslovakia and of their main performer Josef Weiss (ca. 1912, Veľké Kapušany – 1985 Netanya), who was a hazzan (cantor) in synagogues in Vienna, Budapest, Prague, Jerusalem, Ramat Gan, Manchester, and New York, but has remained mostly unknown to music history. It shows how these two 78-rpm records stand at the core of Weiss’s grandson’s family / music / memory project, which has revealed and prepared to reissue 52 audio recordings to preserve his grandfather’s legacy. While following these and other digitized and technologically modified recordings of Weiss on their recent path between the Czech Republic, Israel, Hungary, and the US, the article sheds light on how this case fits into the broader framework of the social life of things and the context of musical remembrance. Already put to use during the life-cycle rituals of Weiss’s children and grandchildren, as well as in a museum exhibition – this family project constructs a fragment of a Jewish sonic past for the present needs of its actors, while being entangled with the current practice of Jewish memory institutions, as well as with the activities of private record collectors and of one ethnomusicologist (myself).